Influence of Regional Financial Management Aspect on Regional Financial Management Transparency: Case Study in SKPD, Buton Selatan District - Mansur, Aziza Syahrani; Kusumawati, Andi; Wahda, Wahda (PT. Riset Press International, 2023)
This research aimed to assess the impact of regional financial statement presentation, accessibility of regional financial statements, internal control, the implementation of performance-based budgeting, and the implementation of accrual-based government accounting standards on the transparency of regional financial management. Data for this research were collected through a survey using questionnaires. The study population consisted of all employees in the Regional Work Units (SKPD) of the city of Yogyakarta. The sampling technique employed a nonprobability sampling method known as purposive sampling. The sample comprised structural officers and employees/staff responsible for accounting/administrative financial functions, each with a minimum of one year of experience in each SKPD in Buton Selatan. A total of 77 questionnaires were processed for analysis. Data analysis involved multiple linear regression. The results of the regression analysis indicated that regional financial statement presentation had no significant effect on the transparency of regional financial management. In contrast, the accessibility of regional financial statements was found to have a significant positive effect on transparency. Additionally, internal control was not found to have a significant impact on transparency, nor did the implementation of performance-based budgeting. However, the implementation of accrual-based government accounting standards was found to have a significant positive effect on the transparency of regional financial management.